MONETARY OUTLOOK: INTERNAL VALUE OF MONEY STABILITY COMPARISON IN USA - Sasongko, Budi; Widarni, Eny Lestari; Bawono, Suryaning (JBFEM, 2021)
This paper aims to study the transformation of money in the United States using qualitative content analysis and predict the stability of the internal exchange rate of money by comparing the internal exchange rate of commodity money proxied by gold against crude oil internally. The exchange rate of fiat money proxied by the USD against crude oil and the internal exchange rate of synthetic money proxied by bitcoin against crude oil use the autoregressive threshold (TAR) method in the exchange period. In the great depression, fiat standards, subprime mortgage crisis, Europe experienced a debt crisis until 2017 (1960 - 2017). We compare the internal stability of money for each period in the aggregate using TAR to describe the overall fluctuation of internal exchange rate stability. So it can be seen that the behavior of data movements based on the crisis period experienced is the basis for predicting the stability of the internal exchange rate in the future.